Factors Influencing the Implementation of Infant Warming Devices Among Healthcare Workers in Malawian Hospitals - Alinane Linda Nyondo-Mipando PhD; Mai-Lei Woo Kinshella MSc; Sangwani Salimu MPH; Brandina Chiwaya NMT; Felix Chikoti NMT; Lusungu Chirambo; Ephrida Mwaungulu NMT; Mwai Banda BSc; Tamanda Hiwa MMed; Marianne Vidler PhD; Elizabeth M. Molyneux MD; Queen Dube PhD; et al. (SAGE Publishing, 2024)
Objectives . Preterm infants are at risk of hypothermia. This study described the available infant warming devices (IWDs) and explored the barriers and facilitators to their implementation in neonates in Malawi. Methods . A qualitative descriptive study was conducted among 19 health care workers in Malawi from January to March 2020. All interviews were digitally recorded, transcribed, and managed using NVivo and analyzed using a thematic approach. Results . The warming devices included radiant warmers, Blantyre hot-cots, wall-mounted heaters, portable warmers, and incubators. Inadequate equipment and infrastructure and gaps in staff knowledge and capacity were reported as the main challenges to optimal IWD implementation. Caregiver acceptance was described as the main facilitator. Strategies to optimize implementation of IWD included continuous practical training and adequate availability of equipment and spare parts. Conclusion . Implementation of warming devices for the management of neonatal hypothermia is effective when there are adequate human and material resources.